The Relationship Between Parenting Styles And Anxiety Levels In Children Aged 3-6 Years During Hospitalization - Dior Manta Tambunan; Febri Theresia Sihaloho (CV. AFDIFAL MAJU BERKAH, 2026)
Hospitalization is a stressful experience for children, especially when they have to undergo disruptive procedures, which often cause anxiety that affects the child's physical and mental health. This can create a traumatic experience related to hospitalization. This study aims to identify the relationship between parenting styles and anxiety levels in preschool-aged children during hospitalization. The method used in this study is quantitative with a cross-sectional survey design. A total of 52 children aged between 3-6 years (preschool) who were treated at Private Hospital